Evaluation of Bcl-2, Mcl-1, and Bax as Potential Biomarkers in Chemo Radiotherapy Induced Oral Mucositis in Head and Neck Cancer Patients: A Pilot Study - R Deepika; Sreedevi Dharman; Selvaraj Jayaraman (Wolters Kluwer Medknow Publications, 2024)
Background: Oral mucositis (OM) is an acute debilitating side effects of chemoradiotherapy (CRT) in head and neck cancer (HNC) patients. Salivary biomarkers are noninvasive and aid in early diagnosis and disease prevention. Objective: This study analyzed Bcl-2, Mcl-1, and Bax as potential biomarkers in CRT-induced OM in HNC patients. Methods: Forty-six HNC patients receiving CRT with OM were evaluated using WHO grading. Two time points were observed for saliva sample collection: Day 0 (prior to CRT) and Day 30 (CRT with OM) and from 46 healthy volunteers. Using an enzyme-linked immunosorbent assay (ELISA), levels of Bcl-2, Mcl-1, and Bax were measured. Oral mucositis progression was analyzed using Friedman's test, and statistical significance between means of different salivary marker was determined using the ANOVA test. Results: From Day 0 to Day 30, grades of OM were statistically significant (P < 0.05). Apoptotic biomarkers showed statistically significant higher expression of proapoptotic regulator Bax and lower expressions of antiapoptotic markers Bcl-2 and Mcl-1 on Day 30 (severe OM) compared to Day 0 and healthy controls (P < 0.0001). Conclusion: Our research showcased Bax, Bcl-2, and Mcl-1 as early predictive indicators of OM, and targeted drugs should be developed against these to prevent onset and severity of oral mucositis that improves patients quality of life.